KENDALA GURU DALAM MENERAPKAN MODEL KOOPERATIF TIPE MAKE A MATCH DALAM MATA PELAJARAN SOSIOLOGI KELAS XI IPS SMAN 2 SOLOK SELATAN - Amelia, Sandra; Sarbatinil, Sarbatinil; Erningsih, Erningsih (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
This research is motivated by the fact that student learning success is always a problem in every subject, especially sociology in class XI IPS at SMAN 2 Solok Selatan, so that teachers must have other learning models that encourage students to work collaboratively in achieving learning goals. The purpose of this study was to identify the constraints and solutions faced by teachers in applying the make a match type of cooperative learning model in sociology class XI IPS at SMAN 2 Solok Selatan. The approach used in this study is a descriptive qualitative approach, with a total of 6 informants which was carried out by means of purposive sampling. The types of data used are primary data and secondary data with data collection methods: observation, interviews and document study. Meanwhile, data collection techniques were carried out by observation, interviews, and document studies. The data analysis technique used is the Miles and Huberman model, namely data collection, data reduction, data presentation, drawing conclusions. The results showed that the teacher's constraints in applying the make a match type cooperative learning model in sociology class XI IPS at SMAN 2 Solok Selatan were difficulties in controlling the class, low student motivation, less effective time management and lack of workshops on learning models . As for the solutions made to overcome these obstacles, namely conditioning the class well so that the class atmosphere is not noisy, designing cooperative learning model activities of the make a match type, setting lesson time limits and attending workshops specifically for teachers.